AUDIT ENERGI DI MESIN KERTAS - Farah Dina, Sari
Energy audit is the effective way to be conducted in carrying out of energy efficiency program. Drying unit as the biggest energy consumer in paper machine represents the process unit using steam to evaporate water from the paper sheet. Evaporation is done because water cannot released again by two previous way namely in gravitation (forming unit) and mechanical (pressing unit). This research is applying an energy audit to process unit for paper machine drying unit performance evaluation. Data obtained from the audit is used to determine mass and energy balance. Besides getting distribution of the energy consume, these audit also intends to get the performance drying unit based on specific energy consumption (SEC). SEC obtained to be expressed as actual SEC and conducted benchmarking to abroad factory from literature. Study to be perceived covering the dewatering process optimization before and after drying unit, study to air system and last is steam distribution system by application of thermocompression. Result of audit at 5 (five) paper mills indicated that the SEC influenced by machine speed, moisture content of paper sheet enter the drying unit, final moisture content of product, system of air handling, the rate of air leakage on the closed-hood system. SEC in ton steam per ton evaporated of paper mills that produce paper with low basis weight (paper mill A and B) coming near standard value (1.3), but paper mills that produce heavy weight product (C, D and E) residing in far above standard. Except paper mill producing chipboard (paper mill E), all other paper mills have the SEC in ton steam per ton product is in the range of standard value (1.8 - 2.2). The decreasing of paper sheet moisture content enter drying unit up to 3% such as those which is done by paper mill B have been able to reduce the steam consumption of 12%. The increasing final moisture content of product from 4% becoming 5% can reduce the steam consumption 1%. On the closed-hood system, like paper mill B, the rate of air leakage is above of standard condition (48% vs up to 30%). The study for application of thermocompression system at one of paper mill C dryer group reduced steam consumption of 5%.